Translation, rewriting and the manipulation of the Singaporean Chinese identity: a case study from "Six Letters" (2018) - Lim, Ka Min (Nanyang Technological University, 2023)
The concept of cultural identity is fluid and ever-changing. A culturally-diverse society, ancestral traditions and ideas, and an amalgamation of government policies have allowed the adaptable Singaporean Chinese to develop their own unique identity. This constitutes the Singaporean Chinese identity, which has received substantial attention in the academic field and media in recent years. Through a comparative study of two letters written by two young journalists to each other as well as their translations, taken from the Six Letters (2018) project by Singapore Press Holdings’ flagship papers The Straits Times and Lianhe Zaobao, we examine how translation, rewriting and manipulation can affect the understanding of “Chinese privilege”. A close examination of the letters indicates differences in approaches in translation between the two publications. The study reveals and suggests that there is a complex and intriguing interplay between language ideologies and the political economy. Furthermore, the concept of Singaporean Chinese identities calls for more empirical and comparative studies. The paper concludes by highlighting patronage, the ideology of the two publications, as well as challenges of journalists doubling up as translators. Keywords: Singaporean Chinese identity, Six Letters, ideology, manipulation, translation